2022
DOI: 10.3389/fonc.2022.999343
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-combination therapy for previously untreated metastatic nonsquamous NSCLC: Real-world outcomes at US oncology practices

Abstract: ObjectivesThe availability of immunotherapies has expanded the options for treating metastatic NSCLC, but information is needed regarding outcomes of immunotherapy for patients treated outside of clinical trials. The aim of this retrospective study was to evaluate the outcomes of therapy with first-line pembrolizumab plus pemetrexed and carboplatin (pembrolizumab-combination) for patients with metastatic nonsquamous NSCLC in the real-world setting of oncology clinics in the United States (US).MethodsUsing deid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…All newly diagnosed patients had poor sleep quality, which was associated with daily fatigue. As previously observed in other immunotherapy studies, patients with high a PD-L1 status (≥80%) have a faster response and a prolonged response [ 24 ]. We stratified our patients, as in previous studies, into three categories in order to perform our analysis [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 58%
“…All newly diagnosed patients had poor sleep quality, which was associated with daily fatigue. As previously observed in other immunotherapy studies, patients with high a PD-L1 status (≥80%) have a faster response and a prolonged response [ 24 ]. We stratified our patients, as in previous studies, into three categories in order to perform our analysis [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 58%
“…Somewhat lower survival rates than in the clinical trials and our analysis were reported in two analyses based on the US Flatiron Health Database, with a median OS of 9.3-12.0 months [31][32]. From the same database, a median OS of 17.2 months was reported for PD-(L)1 combination therapy in NSQ NSCLC [33]. Major differences with the current study include geography, complete information on ECOG PS in the present study, and that our study is population-based, unlike database studies only including patients from a specific US electronic health record system.…”
Section: Discussionmentioning
confidence: 56%
“…In the subgroup of patients with expression of PD-L1 <1%, the objective response rate was 26%, median PFS was 5 months (95%CI 4.5-6.2) and the median OS was 13.2 months (95%CI 10.9-19.9). In the subgroup with expression of PD-L1 in the range of 1-49%, median OS was 16.0 months (95% CI 11.7-22.1); it was not indicated whether observed differences were statistically significant ( 20 ), but the difference is meaningful numerically. In the above study, among patients with negative PD-L1 expression, 41% of patients received systemic treatment after failure of immunochemotherapy, a slightly higher proportion than in our group (31%) and in the previously cited study by Waterhouse et al.…”
Section: Discussionmentioning
confidence: 97%
“…Liu et al. presented a group of 377 patients with non-squamous metastatic NSCLC – 24% of the patients did not have an evaluation of PD-L1 expression, and 27% had low PD-L1 expression ( 20 ). The median overall survival (OS) was 17.2 months (95% CI, 13.6-19.9) in the general population.…”
Section: Discussionmentioning
confidence: 99%